Faktor Risiko Kegagalan Pengobatan Malaria Di Kecamatan Mlati Kabupaten Sleman Daerah Istimewa Yogyakarta - Sri Wandansari Agustini, Prajoga dan Atik Choirul Hidajah (Berita Kedokteran Masyarakat (BKM), 2004)
Background: Mlati Subdistrict Sleman District was declared as a malaria endemic area in 2003, there was an increase in the number of cases to 310. Among these cases, 33.9% turned out to be of falciparum malaria type. Medical treatment has been administered to all cases; however, records indicated that 40.95% of the cases have exhibited signs of treatment failures as indicated by parasitaemia since the seventh to 28'h day of the treatment. Based on such evidences and to prevent future relapse, a study need to be performed to learn the factors which contribute to the failures in the treatment of falciparum malaria cases.Methods: Case-control design was employed in this investigation to research subjects which consists of all falciparum malaria cases who did not show any complications and who still underwent anti-malarial drug treatment, who have shown positive results in blood-slide tests during data collection in the period of November 2002 to April 2003. Control subjects consists of falciparum malaria cases without any signs of complications who have been completely cured at the same time (86 cases). The control-group was selected by matching their ages, sexes, residences, and also using a simple random sampling procedure. Factors investigated included: compliance to medication, means of taking medication, dosage accuracy, buying anti-malarial drug in stores or shops, previous history of anti-malarial medication and those who travel or stay in resistant areas. Data were collected through interviews and record tracking. Data were analyzed using multiple logistic regression analyses.Results: Bivariate analyses concluded that those considered as the risk factors which contribute to failures of the treatment of falciparum malaria without complications were compliance to medication (OR: 10.9), means of taking medication (OR: 3.1), length of medication (OR: 4.5), dosage accuracy (OR: 5.8). Multivariate analyses concluded that compliance to medication (OR: 13.6) and previous history of anti-malaria medication (OR: 5.6) have contributed to the failures of treatment of falciparum malaria without complications.Recommendations: The knowledge on influencing factors and risk factors which contributed to failures of medical treatment can be considered by health institutions administering treatment of falciparum malaria with no complications to the designated procedures more intensively, to prevent an increase of medical failures. Improvement of the skill of health personnel who administer medical treatment in the provision of EIC to cases and their family members. There is a need to launch a more comprehensive study involving larger sample size and other variables or factors which were not covered in this investigation.Keywords: risk factors, treatment failures, falciparum malaria